2016
DOI: 10.4103/2008-7802.194883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pomegranate seed oil on metabolic state of patients with Type 2 diabetes mellitus

Abstract: Background:Rapid increasing prevalence of diabetes mellitus is a serious health concern in the world. New data determined that the pathogenesis of diabetes mellitus is chronic low-grade inflammation, resulting insulin resistance. Pomegranate seed oil (PSO) has anti-inflammatory effects; though it may reduce insulin resistance and improve glycemia in diabetes mellitus. The present study has been designed to investigate the effects of PSO as a natural dietary component on metabolic state of patients with Type 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The total number of subjects included in each study ranged from 14 to 74 subjects. Among the included studies, fifteen studies reported the FBG outcome [ 27 , 28 , 30 32 , 39 46 ], 8 reported FBI values [ 29 31 , 41 43 , 45 , 46 ], 3 reported HbA1c [ 27 , 41 , 43 ] and 7 reported HOMA-IR [ 29 , 31 , 41 43 , 45 , 46 ]. The mean age of participants in each trial ranged from 30 to 70 years, with differing age ranges in most studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of subjects included in each study ranged from 14 to 74 subjects. Among the included studies, fifteen studies reported the FBG outcome [ 27 , 28 , 30 32 , 39 46 ], 8 reported FBI values [ 29 31 , 41 43 , 45 , 46 ], 3 reported HbA1c [ 27 , 41 , 43 ] and 7 reported HOMA-IR [ 29 , 31 , 41 43 , 45 , 46 ]. The mean age of participants in each trial ranged from 30 to 70 years, with differing age ranges in most studies.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of participants in each trial ranged from 30 to 70 years, with differing age ranges in most studies. Of the 16 trials included in the current meta-analysis, 11 studies used pomegranate juice as a supplement (the dosage ranged from 120 to 500 ml/day) [ 27 , 28 , 30 32 , 40 , 41 , 44 46 ], 2 studies used pomegranate seed oil as treatments (the dosage ranged from 400 to 2000 mg/day) [ 29 , 43 ], and 3 studies utilized pomegranate extract as the intervention (the dosage ranged from 710 to 1420 mg/day) [ 39 , 42 ]. The duration of the pomegranate intervention varied from 1 to 12 week (median: 5.5 week).…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus has now reached an epidemic level in both developing and developed countries. Due to the pandemic level and macro- and micro-vascular complications caused by diabetes mellitus, it could emerge as a worldwide issue with huge economic and social costs [1]. Dietary approaches can be a successful strategy to diminish the risk of diabetic complications [2].…”
Section: Introductionmentioning
confidence: 99%
“…Increased free fatty acid flux secondary to insulin resistance and increased proinflammatory adipokines and cytokines from enlarged adipose tissue may be the underlying determinants of this interrelationship. [ 7 8 ]…”
Section: Introductionmentioning
confidence: 99%